Analysis of the Current Account on the Balance of Payments in East Java Province - Arifki, Ogy Dwi; Yasin, Muhammad (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
This study aims to analyze the current account on the balance of payments in East Java province. The method used is data analysis and literature study. The results of the analysis show that the current account on the balance of payments in East Java province has increased (surplus) from 2018 to 2019, but from 2019 to 2020 the current account data has decreased (deficit). This is because there are many factors, including the economic decline due to the Covid-19 outbreak which has hampered the pace of economic growth in East Java province and there are other factors such as the lack of public awareness of paying taxes, this has also caused the rate of economic growth.